Masterpieces : painting and sculpture Kunsthalle Mannheim - Städtische Kunsthalle, Mannheim (Cologne : Wienand, 2013)
The historical ambiance of the Kunsthalle Mannheim, established in 1909, is home to a magnificent collection of international art from the early nineteenth century to the present day. The collection, with its 2,150 paintings, contains major works of the Romantic period, French Impressionism, German Expressionism and international modernism. The exquisite collection of sculptures covers top works by Auguste Rodin, Wilhelm Lehmbruck, Henry Moore and Richard Long.
boek